(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Food circulated in Indonesia, is not well warranted in safety. In the year 1999 Badan POM found 13,7% of food products were not fulfill the labeling regulations. All problems needed the attention not only from government, producers but also consumers. Housewives have to be careful and pay attention on kinds of all food that consumed by family’s members. Housewife’s knowledge about food labeling is necessary in order to act and choose appropriately the healthy food. The purposes of this research were to learn the relation between knowledge, attitude and housewife action in choosing packaged labeled food. This research also learn the information source about food labeling, kinds of packaged food which is usually bought by the respondent, frequently bought the packaged food and also respondent opinion about price of packaged food. This research was the observational research. The population were housewives who visit and shop at Super Indo supermarket at Surabaya Plaza (in 2 weeks period). The samples were housewives who were purchasing packaged food (59 persons in 2 weeks period). The data were collected by using questionnaire and analyzed by Spearman correlation test (α=0,05). The results show that most of respondents have low knowledge (81,4%), improperly action (67,8%), but good attitude (91,5%). There was no significant correlation between knowledge and action (p=0,081, a=0,05), no significant correlation between attitude and action (p= 0,703, a=0,05). Source of Information about food label obtained by respondent from television/radio (77,9%), packaged food usually bought was milk (52,5%), respondent bought the packaged food more than 4 times in a month (27,1%), because according to their opinion there was cheap enough to buy the packaged food (87,4%). It was necessary to give information about the importance of food labeling to communities by using various media (especially television).